Towards sustainable, solution-processed organic field-effect transistors using cashew gum as the gate dielectric - Faraji, Sheida; Tall, Abdoulaye; Mohammadian, Navid; Seck, Mané; Saadi, Meriem; Tavasli, Aybüke; Erouel, Mohsen; Khirouni, Kamel; Diallo, Abdou Karim; Majewski, Leszek A. (Frontiers in Materials, 2023)
To realize low-cost, environmentally friendly electronic devices and circuits, there is currently a strong trend to explore plant-based dielectric materials because they can be responsibly sourced from agricultural or forest vegetation, are generally water-soluble, and possess good electrical insulator properties. In this contribution, organic field-effect transistors (OFETs) using a biopolymer dielectric obtained from exudates of Anacardium occidentale Linn. trees, namely, cashew gum (CG), are reported. To characterise the physical and dielectric properties of the gum, thin films and metal-insulator-metal (MIM) capacitors were prepared and characterized. To evaluate the material’s performance in OFETs, bottom-gate top-contact (BGTC) p-channel poly [3,6-di(2-thien-5-yl)-2,5-di(2-octyldodecyl)-pyrrolo (3,4-c)pyrrole-1,4-dione) thieno (3,2-b) thiophene]:polymethyl methacrylate (DPPTTT:PMMA) transistors were engineered and studied. The fabricated MIM capacitors display a comparatively high areal capacitance of 260 nF/cm2 at 1 kHz for 130 nm thick films. As a result, the solution-processed DPPTTT:PMMA OFETs favourably operate at 3 V with the average saturation field-effect mobility equal to 0.20 cm2/Vs., threshold voltage around −1.4 V, subthreshold swing in the region of 250 mV/dec, and ON/OFF current ratio well above 103. As such, cashew gum emerges as a promising dielectric for sustainable manufacturing of solution-processed organic FETs.